El ratoncito, la fresa roja y madura y el gran oso hambriento = The little mouse, the red ripe strawberry, and the big hungry bear - Wood, Don, 1945-; Wood, Audrey; Mlawer, Teresa; Canetti, Yanitzia, 1967- (Auburn, Maine : Child's Play Inc., 2011)
Little Mouse worries that the big, hungry bear will take his freshly picked, ripe, red strawberry for himself.
El ratoncito hara cualquier cosa para evitar que el gran oso hambriento le quite su fresa.
Title from cover.
On board pages = En paginas de carton duro.
Translation of: The little mouse, the red ripe strawberry and the big hungry bear.
Originally published: Swindon : Child's Play (International) Ltd., 1984.
Bilingual text in English and Spanish.
Keywords: Mice -- Juvenile fiction; Ratones -- Novela juvenil; Strawberries -- Juvenile fiction; Fresas -- Novela juvenil; Bears -- Juvenile fiction; Osos -- Novela juvenil; Spanish language materials -- Bilingual; Materiales en espanol, Bilingues